Planning a Clinical Development Programme for Radiopharmaceuticals: An Analysis of International Guidelines and Expertise - D. V. Goryachev; I. V. Lysikova; A. A. Chernaia; D. D. Kushnir (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Current scientific knowledge in the field of molecular biology and the associated manufacturing and technical capabilities enable the development of radiopharmaceuticals (RPs) with high specificity to the target organs, tissues, and receptors. The development of novel RPs requires mandatory clinical trials. However, at the moment, the Russian Federation and the Eurasian Economic Union (EAEU) lack documented guidance for drafting application dossiers for obtaining authorisation for clinical trials of RPs. There is a need for guidelines that will set forth recommendations for planning comprehensive clinical development programmes and regulate data submission requirements for clinical trials of various types of RPs.AIM. This study aimed to explore whether the methodological approaches outlined in international regulatory documents can be used to inform the development of a Russian guideline for the conduct of clinical trials of RPs.DISCUSSION. The authors conducted an extensive analysis of the Russian and EAEU laws and regulations and the guidelines by regulatory agencies in Europe (European Medicines Agency, Swissmedic), the US, and Canada that included provisions for planning and conducting clinical trials of RPs. This analysis identified the key considerations defining the clinical development programme for an RP (including its innovation level and administration route). This article describes the main phases of clinical trials and defines the phase-specific aspects of planning clinical trials of PRs. These aspects include the selection of the trial population, endpoints, design, and duration and considerations for special patient populations. The article summarises the requirements for the content of the application dossiers submitted to regulatory authorities to obtain authorisation to conduct clinical trials of RPs. The article outlines typical nonconformities and errors in application dossiers identified during the assessment of RP clinical trial protocols submitted to the Scientific Centre for Expert Evaluation of Medicinal Products of the Ministry of Health of the Russian Federation in 2020–2024.CONCLUSIONS. This comprehensive analysis of the documents regulating the leading regulators’ approaches supplemented with the critical assessment of the Russian experience can serve as a basis for the development of clinical programmes for both novel diagnostic/therapeutic RPs and well-characterised compounds. The considerations presented in the article may be used by experts reviewing clinical trial results and by RP developers.